Optimasi Pemasangan Kabel Internet Antar Daerah Kabupaten Sleman Menggunakan Minimum Spanning Tree - Deddy Rahmadi; Nabila Putri Maharani; Muhammad Rejaus Syifa; Sulthon Aqthoris Sama; Galih Fathurahman Ardiansyah (Journal of Mathematics Theory and Applications, 2024)
Currently, many internet providers use various types of internet cables. Cable Internet uses cable network infrastructure from ISPs such as Biznet, First Media, or Indie Home, while other alternatives use cellular or satellite Internet. One of the advantages of Internet cables compared to these two alternatives is speed, especially fiber optic cables. However, one of the weaknesses of Internet cables is their high price. Therefore, to optimize the costs incurred, it is necessary to find the shortest route to reducing costs. Using the Kruskal algorithm method, the author determines a minimum route of 106 km.